A national survey of neurological monitoring practice after obstetric regional anaesthesia in the UK1. (10th January 2017) - Roderick, E.; Hoyle, J.; Yentis, S. M.
Summary: Neuraxial anaesthesia is widely used in obstetrics and neurological complications are rare. However, when they occur, subsequent investigation and management are time‐critical and correlate with the extent of neurological recovery. The Third National Audit Project recommended the implementation of guidelines in obstetric epidural management, including advice on monitoring for early signs of problems and acting upon concerns. However, no national guideline exists for postoperative management in the obstetric population. We conducted a national survey of monitoring after obstetric neuraxial blockade and the management of an abnormally prolonged block. We received responses from 112/189 (59.3%) obstetric anaesthetic leads invited to participate. We determined that post‐neuraxial blockade monitoring in the UK is highly variable: only 63/112 (56.3%) respondents' units had a monitoring policy in place, although most of these did not undertake formal neurological monitoring, and a range of different monitoring methods and schedules were employed. In 12/63 (19%) local policies, the first review of neurology was performed at the standard postoperative visit the following day, and 66/112 (58.9%) units had no protocol in place to address emergency management of abnormally prolonged neuraxial blockade. Where a policy was in place, the initial recommended action and the type of imaging used were variable.